Characteristics of Infill Pattern and Density Utilizing the Commercial Lattice Structure of 3D Printers for Application in 3D-Printed Insoles - Auysakul, Jutamanee; Srewaradachpisal, Satta; De Becker, Oriana; Adrian Killen, Bryce; Chatpun, Surapong (International Journal of Online and Biomedical Engineering (iJOE), 2026)
The increased prevalence of unhealthy lifestyles has led to an increase in numerous diseases, especially diabetes mellitus. Hyperglycemia causes peripheral neuropathy, which frequently results in loss of sensitivity in regions such as the plantar foot and increases the risk of diabetic foot ulceration. These ulcers are typically managed with therapeutic insoles designed to reduce plantar pressure. Conventional insoles typically consist of multiple layers of various soft materials. The concept of a 3D-printed insole is introduced in this study, especially regarding infill and infill density. The commercial lattice structures in 3D printers, such as honeycomb, rectilinear, and gyroid, with between 14% and 22% infill density, are considered in this work to study the mechanical behavior in terms of the ability to withstand compressive load and energy absorption capability. The honeycomb pattern with 22% infill density provides good results in comparison to other patterns. This study also verifies that a 3D-printed insole, featuring an optimized infill pattern and density, significantly reduces both the peak and mean plantar pressure in the hindfoot region during the midstance phase of the gait cycle, as observed in both the finite element (FE) model and experimental results. Significantly, this study provides guidelines on the characteristics of energy absorption and the compressive load of infill pattern and density for the 3D-printed structure to develop the orthotic insole in future studies.